The Stock Market and Exchange Rates in Five South Asian Countries - Firmansyah, Firmansyah; Oktavilia, Shanty (Universitas Muhammdaiyah Surakarta, 2017)
The composite price index and return of stocks are the important indicators, both as a measure of the companys portfolio performance, as well as an indicator of macroeconomic health and the aggregate investment. In addition, the stock prices are also influenced by macroeconomic variables and one of the most important is the exchange rates. The objective of this study is to determine the behavior of exchange rate affects the stock returns in Southeast Asia, pre and post of the 2008 world financial crisis. By employing the daily stock market return in Indonesia, Malaysia, the Philippines, Thailand, and Singapore more than seventeen years from 1 September 1999 to 31 March 2017, this study utilizes Engle-Granger error correction model and cointegration approach to investigate and compare the long and short run of the structural effect of the exchange rates on stock returns. To differentiate the behavior of variables between pre and post occurrence of 2008 world financial crisis, the estimation of the model is divided into two periods. This study finds that the exchange rate growth influence the stock returns in the long and short run, and proves that the cointegration between the two variables exist in all countries. The study has the implication that the exchange rate, which the one of the fundamental measures of a countrys macroeconomic health, is an important determinant of influencing stock return, even its effects are responded by the stock return in one day.